12 epic races - Slingerland, Janet (Epic adventures., 2019)
Highlights twelve epic races from around the world including the Indianapolis 500 in Indiana, the Vendée Globe, La Ruta de Los Conquistadores in Costa Rica, and the Mongol Derby in Mongolia. Contains a world map, color photographs, statistics, and a glossary.